Impact of rooftop photovoltaics and centralized energy storage on the design and operation of a residential CHP system. (15th July 2018) - Ondeck, Abigail D.; Edgar, Thomas F.; Baldea, Michael
Highlights: Study impact of energy storage and PV on the design and operation of a CHP plant. Real residential energy demand scenarios used to capture variability and uncertainty. Simultaneous optimization of design and operation solved via bilevel decomposition. TES decreases costs as well as improves efficiency of neighborhood-level CHP plant. Abstract: With expected further increases in renewable generation, researchers have been investigating energy storage as a means to improve grid resiliency and harness renewable resources. Energy storage has the potential to both shift renewable generation in time and level peaks in demand. In this paper, we study the impact of centralized energy storage and rooftop photovoltaics on the design and operation of a natural-gas powered Combined Heat and Power (CHP) plant as an integrated utility supplier for a residential neighborhood operating in island mode. Utilizing a novel simultaneous optimization approach for the plant design and operating strategy, the CHP plant is optimized to meet a time-dependent energy demand profile characteristic of residential energy use. This multi-scale optimization problem is solved using a tailored bilevel decomposition method. The results reveal the most economic energy storage method, while highlighting the need to decrease the cost of rooftop photovoltaic panels.